The existence of standard-biased mortality ratios due to death certificate misclassification: a simulation study based on a true story - Deckert, Andreas (BMC medical research methodology, 2016)
Mortality statistics are used to compare health status of populations; optimally, they base on individual death certificates. However, determining cause of death is error-prone. E.g. cardiovascular disease (CVD) death determination is characterized by sensitivity (SE) and specificity (SP) lower than 85 %. Furthermore, differential misclassification may be present in case of homogenous target populations. We investigate the bias of standardized mortality ratios (SMR), based on real-world data.